Development of a Human-Agent Interaction System including Norm and Emotion in an Evacuation Situation (Student Abstract) - Sinyabe Pagou, Ephraim; Kamla, Vivient Corneille; Tchappi, Igor; Najjar, Amro (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
Agent-based modeling and simulation can provide a powerful test environment for crisis management scenarios. Human agent interaction has limitations in representing norms issued by an agent to a human agent that has emotions. In this study, we present an approach to the interaction between a virtual normative agent and a human agent in an evacuation scenario. Through simulation comparisons, it is shown that the method used in this study can more fully simulate the real-life out come of an emergency situation and also improves the au thenticity of the agent interaction.